VLADIVOSTOK STUDENTS' VALUE SYSTEM - Oksana O. Martynenko; Olga A. Korotina (Высшее образование в России)
The paper dwells on students' value system issues, priority of education and students' involvement in social practice. A methodological foundation of the research has been laid by the conceptual idea of D.A. Leontiev, who discovered that value matter translation was by means of activity. It has been established during the conducted study that the students' value system is focused mainly on hedonic, material and family values. Thereafter moral, ethical and aesthetic values are of low importance. On the other hand, the priority of values, concerning personal life, health, safety, self-development and self-improvement can be set, whereas social values such as democracy improvement, freedom growth, more humane society, active civic position of young people are less important. This testifies an increase of a subjective factor of value system and a risk of further society dehumanization. The education priority are unique education in prestigious institute of higher education, tuition-free education preference; location of higher education institute plays a great role as well as a positive sociocultural environment, IT support level of educational process. Future expectations are prestigious, interesting and well-paid work, which meets personal abilities and possibilities, with student's awareness of the importance of professional skills, experience and scientific knowledge.